The Emperor's Tomb : a Novel - Berry, Steve 1955- (New York : Ballantine Books, 2010)
Former government operative Cotton Malone teams with old heartthrob Cassiopeia Vitt on a dangerous mission to retrieve a priceless Chinese lamp from the third century B.C.E.
Keywords: Malone, Cotton (Fictional character) -- Fiction; Booksellers and bookselling -- Fiction; Antiquarian booksellers -- Fiction; Kidnapping -- Fiction; Ransom -- Fiction; Suspense fiction; Denmark -- Fiction; Pakistan -- Fiction; China -- Fiction; Suspense fiction